Quercetin Compound of Okra Fruit (Abelmoschus esculentus L.) as Potential of Antioxidant and Antimicrobial - Astutiningsih, Christina; Kristanti, Jesi; Ariani, Winda Ludfi (UIN Sunan Gunung Djati Bandung, 2023)
Respiratory tract infections can be caused by various microbes including Staphylococcus aureus bacteria and Candida albicans fungus. The treatment can use antibiotics or medical plants. Okra plants especially the fruit, are plants with antioxidant and antimicrobial activity caused by one of the flavonoids namely quercetin compounds. The purpose of this study was determine the total flavonoid, identify the isolate, and test the antioxidant and antimicrobial activity of the quercetin compound isolated from okra fruit. The result of the measurement of the total flavonoid content of the diethyl ether fraction obtained an average of 54.8723 Â± 0.8059 mg QE/g and the ethyl acetate fraction obtained an average of 99.3155 Â±1.4518 mgQE/g. The isolated flavonoid from okra fruit had antioxidant power with IC50 of 31,4 ppm, antibacterial activity against Staphylococcus aureus with inhibition zone diameter of 10,372mm; 13,964 mm; and 15, 392mm (1%:5%:10%), and the antifungal Candida albicans with inhibition zone diameter of 9,104mm; 284mm; and 11,380 mm (1%:5%:10%). Flavonoid isolates from Okra Fruit, namely quercetin compounds had strong antioxidant and antimicrobial activity.